Global knowledge-intensive business services trade flows. The revealed competitive position of Europe and Central and Eastern Europe - Brodzicki, Tomasz (Quaestiones Geographicae, 2024)
The paper analyses global trade flows in knowledge-intensive business services (KIBS) over the period 2005 to 2021, focusing on the competitive position of Europe in general with additional emphasis on Central and Eastern Europe (CEE). Using data from the OECD-WTO Balanced Trade in Services (BaTIS) database, the study examines major global exporters and their revealed comparative advantages (RCA), as well as the structure and shifts in the structure of intra- and extra-continental trade flows. We establish some stylised facts. The results indicate that Europe in 2021 was still the largest KIBS exporter globally, however, with declining shares due to Asia and the Americas’ growth over the analysed period. The article further explores the competitive position of the CEE region which became an integral part of the sector in Europe and a favourite destination for nearshoring as well as backshoring projects. We conclude with a set of general policy recommendations. The EU, specifically, should focus on fostering innovation, digital transformation, and skills development by enhancing R&D support, investing in digital infrastructure, and promoting science, technology, engineering and mathematics (STEM) talent pool development to strengthen, in particular creation of high-value-added services in KIBS sectors.